The Effect of Additives on Denture Base Resin Properties - Hussain, Wafaa A; Hashim, Furqan Salim (Al-Nahrain Journal of Science, 2018)
Numerous studies have been carried out on studying the effect of glass fiber and ZrO2 Nano-particles alone on the mechanical properties of PMMA, to date, no investigations were made that have studied the mechanical properties of PMMA reinforced with glass fiber and zirconium oxide together as a hybrid composite.In this research the effect of addition of glass fibers (woven and chopped) and Zirconium oxide Nano-particles (ZrO2) with different weight percent to the conventional poly (methyl methacrylate) (PMMA) has been evaluated.The conventional acrylic resin was used as 2:1 powder to liquid ratio to prepare pure sample, laminate composite prepared by using woven glass fiber (8wt%, 12wt%), fiber-reinforced composite fabricated by chopped glass fiber (8wt%, 12wt%), particle-reinforced composite prepared by using ZrO2 Nano-powder (1, 2, 3) wt%, and the hybrid composite fabricated by using glass fiber as woven or chopped of the two form with ZrO2 Nano-particles. The flexural strength (F.S.) was measured by using three point-bending test. The mechanical test done in order to compare the flexural strength between pure and composite samples. The form of glass fiber with the same weight percent affects the mechanical properties values. Reinforcing PMMA with woven glass fiber and zirconium oxide increase flexural strength, while incorporation of chopped glass fiber decrease the flexural strength. Using the two materials together as a hybrid composite recorded very high raises of flexural strength values. From the results, it's possible to syntheses a denture base resin with good aesthetic and high mechanical properties from fiber and ZrO2 Nano-particles.